2022
DOI: 10.1002/eji.202149774
|View full text |Cite
|
Sign up to set email alerts
|

Human cDC1s display constitutive activation of the UPR sensor IRE1

Abstract: The intracellular mechanisms safeguarding DC function are of biomedical interest in several immune-related diseases. Type 1 conventional DCs (cDC1s) are prominent targets of immunotherapy typified by constitutive activation of the unfolded protein response (UPR) sensor IRE1. Through its RNase domain, IRE1 regulates key processes in cDC1s including survival, ER architecture and function. However, most evidence linking IRE1 RNase with cDC1 biology emerges from mouse studies and it is currently unknown whether hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Even though the IRE1/XBP1s axis is well-recognized to contribute to innate immune responses upon PRR engagement, most of these studies emerged from work in macrophages and DC subsets that do not belong to the cDC1 lineage [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Reports on activated cDC1s include parasite infection [ 29 ], and we reported that human/mouse cDC1s use IRE1 for optimal proinflammatory cytokine production using pharmacological IRE1 inhibitors [ 10 , 14 ]. To extend these findings and identify efficient IRE1 activators in differentiated cDC1s, we stimulated OP9-DL1 cDCs from ERAI mice with agonists of major families of PRRs: LPS (TLR4 agonist), Poly(I:C) (TLR3 agonist), Curdlan (Dectin-1 agonist), DMXAA (STING agonist), MDP (NOD2 agonist), and CpG (TLR9 agonist).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the IRE1/XBP1s axis is well-recognized to contribute to innate immune responses upon PRR engagement, most of these studies emerged from work in macrophages and DC subsets that do not belong to the cDC1 lineage [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Reports on activated cDC1s include parasite infection [ 29 ], and we reported that human/mouse cDC1s use IRE1 for optimal proinflammatory cytokine production using pharmacological IRE1 inhibitors [ 10 , 14 ]. To extend these findings and identify efficient IRE1 activators in differentiated cDC1s, we stimulated OP9-DL1 cDCs from ERAI mice with agonists of major families of PRRs: LPS (TLR4 agonist), Poly(I:C) (TLR3 agonist), Curdlan (Dectin-1 agonist), DMXAA (STING agonist), MDP (NOD2 agonist), and CpG (TLR9 agonist).…”
Section: Resultsmentioning
confidence: 99%
“…The advent of this methodology prompted us to investigate whether IRE1 activation is a feature that can be modeled in cDC1s fully differentiated in vitro. Along these lines, we recently reported that human cDC1s generated under this methodology spontaneously activate IRE1 RNase [ 14 ], which opens novel avenues for expanding studies of the IRE1/XBP1s axis also in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…ASMCs cultured under the high-stretch or static conditions with or without pretreatment of TUDCA (ER stress inhibitor) were evaluated for mRNA expression levels of genes associated with ER stress and inflammation, which could verify whether ER stress mediated the effects of high stretch on ASMCs via ER stress signaling and airway inflammation [ 50 ]. The mRNA expression level was measured by quantitative PCR (qPCR) with the associated primers purchased from General Biosystems (Anhui, China), as shown in Table S5 [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. These primer sequences used in this study are all obtained from the literature and then checked by NCBI Primer-BLAST ( , freely available for any user, accessed on 5 October 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Several labs meanwhile noted that IRE1 shows a higher basal activity in cDC1s compared to cDC2s [11][12][13][14][15] , still the mechanism explaining this subset speci c activation of IRE1 has remained enigmatic. A recent study proposed that antigen-derived peptides can engage IRE1 in a TAP1-dependent manner by binding the IRE1 lumenal domain upon their import in the ER 14 .…”
Section: Ire1 Is Triggered By Apoptotic Cell Engulfmentmentioning
confidence: 99%